A copper(II) zig-zag metal–organic coordination polymer: synthesis, crystal structure, topology study, hirshfeld surface analysis and survey different conditions on morphology of a novel nano structure [Cu(L)(SCN)(H2O)2]n.2H2O. Issue 2 (1st February 2020) - Souri, Bagher; Hayati, Payam; Rezvani, Ali Reza; Mendoza-Meroño, Rafael; Janczak, Jan
Abstract: One copper(II) coordination polymer compound [Cu(L)(SCN)(H2 O)2 ]n .2H2 O (1) where L stand for 2-pyridinecarboxylic acid, was synthesized following two different experimental methods, branch tube and sonochemical irradiation nano methods. Independently of the methodology used, the same crystalline phase is obtained for each compound. Single crystal X-ray analyses on compound 1 showed that Cu 2+ ions are 6-coordinated. Additionally, H-bonds incorporate the zig-zag chains in 1 into 2D (along (1, 1, 0) direction) frameworks. Topological analysis shows that the compound 1 is 2C1 net. Hirshfeld surface analysis of compound 1 was studied. Also, theoretical and experimental morphology were studied. The thermal stability of compound 1 was studied by thermal gravimetric. Finally, the role of reaction time and temperature on growth and final morphology of the structures obtained by sonochemical irradiation are investigated. The results indicated that particle size was reduced with increasing sonication power, temperature, sonication time and decreasing concentration of reactant.